1987
DOI: 10.1073/pnas.84.10.3112
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and DNA sequence of the mercuric- and organomercurial-resistance determinants of plasmid pDU1358.

Abstract: The broad-spectrum mercurial-resistance plasmid pDU1358 was analyzed by cloning the resistance determinants and preparing a physical and genetic map of a 45-kilobase (kb) region of the plasmid that contains two separate mercurial-resistance operons that mapped about 20 kb apart. One encoded narrow-spectrum mercurial resistance to Hg2+ and a few organomercurials; the other specified broad-spectrum resistance to phenylmercury and additional organomercurials. Each determinant governed mercurial transport function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 29 publications
0
91
0
1
Order By: Relevance
“…(Wang et al, 1987) and B. megaterium (Huang et al, 1999) confirmed that Firmicutes type merA primers, Fi-Fw/Fi-Rv1832 and Fi-Fw/Fi-Rv1892, resulted in amplicons of approximately 395 and 455 bp, respectively (data not shown). The b/g-type new primers worked with pDU1358 merA (Griffin et al, 1987) (data not shown). To test the applicability of the Actinobacteria primers, genomic DNA from the mercury-resistant Streptomyces isolate (Is-BDOE1) from soil B was used in PCR reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wang et al, 1987) and B. megaterium (Huang et al, 1999) confirmed that Firmicutes type merA primers, Fi-Fw/Fi-Rv1832 and Fi-Fw/Fi-Rv1892, resulted in amplicons of approximately 395 and 455 bp, respectively (data not shown). The b/g-type new primers worked with pDU1358 merA (Griffin et al, 1987) (data not shown). To test the applicability of the Actinobacteria primers, genomic DNA from the mercury-resistant Streptomyces isolate (Is-BDOE1) from soil B was used in PCR reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The primer pairs were tested in the laboratory on available merA genes from g-Proteobacteria (merA from Serratia marcessens plasmid pDU1358, cloned into pHG103 (Griffin et al, 1987), kind gift of Dr Tamar Barkay, Rutgers University) and Firmicutes merA genes. Three different merA genes originating from Staphylococcus aureus pI258 (Laddaga et al, 1987), Bacillus sp.…”
Section: Methodsmentioning
confidence: 99%
“…There seems to be no specific ars gene associated with arsI, in contrast to arsD and arsA, which always go together because their functions are interrelated (32). MerB is a C·Hg lyase that confers resistance to organomercurials (33). Although superficially similar to ArsI, MerB is an unrelated enzyme with a different reaction mechanism (34).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial mercury resistance has been found in a wide range of Gramnegative and Gram-positive bacteria. The operon varies in the number of genes present and is usually located on plasmids (3,5,8,19,25) and chromosomes (4,13,18,28); they are often components of transposons (5,11,15,20) and integrons (4,13,18) in a striking diversity of arrangements, often involving duplications and distributions of the enzymes, transporters or regulators among several replicons in one cell. Moreover, two major mer genes, the regulator merR and the merA, which codes the NADPH-dependent flavoenzyme mercuric reductase [E.C.…”
mentioning
confidence: 99%
“…The BLASTn program was used with the initial searcher sequence of the partial sequence of the mercuric reductase enzyme, with length of 1141 base pairs (bp), for the Citrobacter freundii, access number AJ418049 (8). The alignment of the sequences, in which two regions with high similarity had been identified by visual approach in color key alignment score bigger or equal to 200, is shown in Fig.…”
mentioning
confidence: 99%